Open government and citizen participation: an empirical analysis of citizen expectancy towards open government data. (September 2019) - Wirtz, Bernd W.; Weyerer, Jan C.; Rösch, Michael
Citizens are at the heart of open government, and their participation represents a fundamental principle of the latter. Despite their essential role and the great potential benefits open government holds for the public, challenges of use among citizens persist. Previous empirical research has scarcely addressed these issues from a citizen perspective. This study investigates the determinants of open government data use by citizens in Germany. Our results indicate that ease of use, usefulness, as well as transparency, participation and collaboration expectancies significantly determine citizens' intention to use open government data, which in turn positively affects their word-of-mouth intention. Overall, the findings not only contribute to our understanding of citizen behavior in the context of open government research, especially shedding light on the key aspects of citizens' usage intention, but also provide implications for both researchers and practitioners. Points for practitioners: Citizen-based use of open government data (OGD) has multiple facets that practitioners should be aware of. Public administration needs to take account of the important role of accessibility and usability in providing OGD services, with the objective of meeting the major challenge of enabling equal access for all populations via appropriate channels and customization. The content-related preparation of OGD services should seek to enhance transparency, participation and collaboration, raising and shaping respective expectations among citizens. Finally, practitioners should pay particular attention to the opportunities and risks associated with word-of-mouth communication in the context of OGD.